Rito sagrado : ressignificações da liturgia pós-concílio Vaticano II - Oliveira, Ludmilla Silva de (2019)
Ritualization is one of the main institutionalization characteristics of the Catholic Church. His celebrations have always involved sumptuous elements that fascinate with beauty, color and music, valuing and ornamenting the rites. Being thus one of the centers of the discussion of the Second Vatican Council was, precisely, the nature of the catholic liturgy. The dissertation aims through a bibliographical study and empirical research to list the points of divergence of the tridentine mass or the usual mass and the new mass. The bibliographic research will be done by primary and secondary sources and the empirical work initially by semi-structured questions made in the group that follows the Tradition in Sergipe as well as groups that follow the tradition in social networks. The study will be qualitative and quantitative, as it will not only account for these differences, but will analyze the facts and show the social elements that depart from these individuals as they seek the memorization of this rite. The results show a society of conservative customs in different areas: gender, social, educational, political, religious. Finally, I show that far from being just two groups, the diversity of the Catholic prism leads to a set of Christian nomenclatures.